2007
DOI: 10.4141/p06-057
|View full text |Cite
|
Sign up to set email alerts
|

Influence de la densité de semis sur la productivité du pois sec cultivé sous un climat frais

Abstract: Pea production is important in Canada, but this pulse is rarely sown as a pure stand in Quebec. A study was conducted from 1997 to 1999 to evaluate the effect of four seeding rates (50, 75, 100 and 150 grains m -2 ) on the productivity of two semi-leafless pea (Pisum sativum L.) cultivars (Delta and Carneval) and two normal leaf cultivars (Bohatyr and Grande) under a cool climate. Generally, when the seeding rate increased from 50 to 150 grains m -2 , maturity was reached earlier, lodging increased but 1000-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Any benefit of earlier planting to optimize harvest index did not translate to a benefit in grain yield when comparing yield response curves among planting date treatments (Figures 5 and 6). Although plant height was only measured in 2018, it did not vary among seeding rates, which agrees with previous studies (Armstrong & Pate, 1994;Knott and Belcher, 1998;Nleya & Rickertsen, 2011;Pageau, Lajeunesse, & Lafond, 2007). Most pea yield components were negatively correlated with final plant population, as shown in this experiment.…”
Section: Primary Yield Componentssupporting
confidence: 91%
“…Any benefit of earlier planting to optimize harvest index did not translate to a benefit in grain yield when comparing yield response curves among planting date treatments (Figures 5 and 6). Although plant height was only measured in 2018, it did not vary among seeding rates, which agrees with previous studies (Armstrong & Pate, 1994;Knott and Belcher, 1998;Nleya & Rickertsen, 2011;Pageau, Lajeunesse, & Lafond, 2007). Most pea yield components were negatively correlated with final plant population, as shown in this experiment.…”
Section: Primary Yield Componentssupporting
confidence: 91%
“…ANOVA for protein content (Table 3(c)) indicates that seeding density has no effect on protein content. Pageau et al 49 did the same experiment on Canadian peas for three consecutive years. For two years, they also concluded that seeding density has no effect.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the efficiency and profitability of fertilizers depend on other farming practices, such as optimal plant density, productive varieties, and adaptation to local conditions (Blanco-Canqui and Lal 2007). Differences in plant growth, development, and yield were recorded with plant densities and pea cultivars (Park et al 1999;Ayaz et al 2004;Pageau et al 2006).…”
Section: Cabi Agriculture and Biosciencementioning
confidence: 99%
“…Densely planted peas were etiolated as a consequence of light searching. In such case, high plant densities can only be adopted for biomass production (to produce fodder or leaves, where the latter are consumed) (Pageau et al 2006;Ayaz et al 2004). For grain production, Matthews (2003) and DAFF (2016) suggested that 90,000 plants per ha (9 plants per m 2 ) was optimal, while for biomass production, Johnston et al (2002a, b) advised increasing density up 50 to 75 plants per m 2 .…”
Section: N and P Application Improved Pea Growth And Yield Under Degr...mentioning
confidence: 99%